2010
DOI: 10.1111/j.1540-5885.2009.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Designing Visual Recognition for the Brand*

Abstract: The present paper examines how companies strategically employ design to create visual recognition of their brands' core values. To address this question, an explorative in-depth case study was carried out concerning the strategic design efforts of two companies: Nokia (mobile phones) and Volvo (passenger cars). It was found that these two companies fostered design philosophies that lay out which approach to design and which design features are expressive of the core brand values. The communication of value thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(182 citation statements)
references
References 25 publications
6
167
0
9
Order By: Relevance
“…The results also gave strong support to the arguments stated by Fuller et al (2008) [11], Oost et al (2009) [30] and Karjalainen and Snelders (2009) [23] that the community-based product innovation can increase the attractiveness of and confidence in the product produced, because this innovation improve the product characteristics that reflect the characteristics of the community.These results also proved that communitybased peripheral attribute attractiveness has a positive and significant effect on the attractiveness of product, which also provide strong support the research of Nancarrow et al (1998) [28], Rundh (2009) [36], De Angelis (2008) [6] and Seva, Gosiaco, Santos, and Pangilinan (2011) [38]found that the peripheral attributes play a key important role in developing the company's competitiveness advantage. This paper started from the research gap relating to the effect of product innovation to consumer purchase intention, in which there are studies found a significant effect of product innovation on consumer purchase intention, while other studies found no significant effect of product innovation on consumer purchase intention.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results also gave strong support to the arguments stated by Fuller et al (2008) [11], Oost et al (2009) [30] and Karjalainen and Snelders (2009) [23] that the community-based product innovation can increase the attractiveness of and confidence in the product produced, because this innovation improve the product characteristics that reflect the characteristics of the community.These results also proved that communitybased peripheral attribute attractiveness has a positive and significant effect on the attractiveness of product, which also provide strong support the research of Nancarrow et al (1998) [28], Rundh (2009) [36], De Angelis (2008) [6] and Seva, Gosiaco, Santos, and Pangilinan (2011) [38]found that the peripheral attributes play a key important role in developing the company's competitiveness advantage. This paper started from the research gap relating to the effect of product innovation to consumer purchase intention, in which there are studies found a significant effect of product innovation on consumer purchase intention, while other studies found no significant effect of product innovation on consumer purchase intention.…”
Section: Discussionsupporting
confidence: 79%
“…This also confirmed the result of research by Fuller, Jawecki, and Muhlbacher (2007) [11]and Oost, Verhaegh, and Oudshoorn (2009) [30] related to the community role in product innovation that ultimately produce product innovations that improve the characteristics of a product that also reflects the characteristics of the community. Karjalainen and Snelders (2009) [23]stated that introduction of the value of a product can be developed through explicit and implicit visual reference. Explicit reference inherently attaches in features designed with the intention of immediately felt and recognized.…”
Section: Product Innovationmentioning
confidence: 99%
“…Decisions to create brand recognition through product design are influenced by a number of factors. Karjalainen and Snelders [23] examined how Nokia (mobile phones) and Volvo (passenger cars) created visual recognition of their brands through product design. By analysing information collected through press releases, annual reports, Internet pages, and a number of in-depth interviews, they found that the design philosophy of creating visual recognition of brands was different in Nokia and Volvo.…”
Section: Strategic Styling Decisionsmentioning
confidence: 99%
“…While Crilly et al's (2009) research situates the eight general intentions within a broad context, there is research that has examined how companies attempt to elicit strategic intentions to foster brand recognition through product design (Karjalainen and Snelders, 2010). Furthermore, some studies have explored the strategies used by designers to elicit specific intentions through product design; in particular, to elicit the emotion 'surprise' (e.g.…”
Section: Intentionsmentioning
confidence: 99%